Functional reservoir microcapsules generated via microfluidic fabrication for long-term cardiovascular therapeutics. Issue 15 (1st July 2020) - Dinh, Ngoc-Duy; Kukumberg, Marek; Nguyen, Anh-Tuan; Keramati, Hamed; Guo, Song; Phan, Dinh-Tuan; Ja'Afar, Nurdiyana B.; Birgersson, Erik; Leo, Hwa Liang; Huang, Ruby Yun-Ju; Kofidis, Theodoros; Rufaihah, Abdul Jalil; et al.
Abstract : The reservoir microcapsules are fabricated through one-step microfluidic phase separation for long-term cardiovascular therapeutics. Abstract : Cardiovascular disease is a chronic disease that leads to impaired cardiac function and requires long-term management to control its progression. Despite the importance of hydrogels for therapeutic applications, a contradiction between the size of a hydrogel and the amount of loaded drug has been encountered when using conventional fabrication methods. In this study, biocompatible reservoir microcapsules (diameter ∼100 μm) with a large liquid core and polymeric shell were fabricated via a one-step phase separation of poly(ethylene glycol)diacrylate (PEGDA) and dextran within pre-gel droplets through microfluidics. By controlling the process of phase separation, high drug-loading efficiency (∼80%) for long-term release (30 days) of vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) was achieved. Drug molecules were dispersed within the liquid core at a concentration above saturation solubility for sustained delivery via regulation of the shells. Effective therapeutic enhancement of human umbilical vein endothelial cell (HUVEC) and umbilical artery smooth muscle cell (SMC) proliferation and tube formation in vitro promoted rapid cell proliferation and increased the number of migrated cells by ∼1.7 times. Moreover, in vivo blood vessel regeneration for cardiovascular control induced by sustained dual-drug (VEGF and PDGF) delivery to the rat heart was achieved, showing the effectiveness of long-term protein delivery in improving cardiac function and significantly reducing ventricular wall thickness and fibrosis of the infarct region. The ratio of heart tissue scarring was reduced to 11.2% after microcapsule treatment compared with 21.4% after saline treatment in the rat model. By using these reservoir microcapsules, similar sustained delivery of proteins, mRNAs and biologic drugs could be developed for the treatment of a range of long-term chronic diseases and regenerative medicine.